z-Reader: a Mobile Game Suite for Improving Children's Reading Skills and Behavior - Guerra, Fabrício V. de A.; Santos, José Amâncio M.; Guerrero, Dalton D. S.; Figueiredo, Jorge C. A. de (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2018)
This work describes an empirical, educational and technological research conducted within the context of Brazilian formal literacy education problems. The main purpose of the research was to address the question of whether research-specific software for mobile devices could improve disadvantaged children reading related variables. In this regard, zReader, a mobile game suite for reading and storytelling, was developed and validated by means of an experiment with children attending Second and Third grades in a Brazilian public school. Results include positive inferential findings for children’s reading skills improvement and book reading frequency.